2004
DOI: 10.1002/kin.20054
|View full text |Cite
|
Sign up to set email alerts
|

Isoconversional kinetic study of alachlor and metolachlor vaporization by thermal analysis

Abstract: The vaporization kinetics of two acetamide pesticides, namely alachlor and metolachlor, was studied by thermogravimetric analysis under nonisothermal conditions (using heating rates between 1.0 and 10 K min −1 ). A model-free isoconversional method of kinetic analysis was proposed, and activation energy dependences on the extent of conversion α for nonisothermal experiments were given. An increase in activation energy is shown for alachlor from 50 to 60 kJ mol −1 , while E values do not significantly vary in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Similar type of effect is observed in the study of dichloroglyoxime (Pourmortazavi et al, 2007). The value of activation energy E a changes slightly with a which suggests that the vaporization stage is a single step (Sbirrazzuoli et al, 2005). The average values of E a energy of vaporization are 26.92 ± 1.90 kJ mol À1 (0.20 6 a 6 0.90, Friedman method).…”
Section: Model-free Analysissupporting
confidence: 56%
“…Similar type of effect is observed in the study of dichloroglyoxime (Pourmortazavi et al, 2007). The value of activation energy E a changes slightly with a which suggests that the vaporization stage is a single step (Sbirrazzuoli et al, 2005). The average values of E a energy of vaporization are 26.92 ± 1.90 kJ mol À1 (0.20 6 a 6 0.90, Friedman method).…”
Section: Model-free Analysissupporting
confidence: 56%
“…TG experiments carried at constant heating rate are very suited to perform kinetic analyses such as isoconversional [21][22][23][24] and Kissinger [25] methods to obtain the activation energy of the process. We will analyse the limitations of using these methods to determine the evaporation enthalpy.…”
Section: Introductionmentioning
confidence: 99%
“…78 energies derived from DSC and FT-IR agree well whereas TMA data give rise to markedly smaller values. Sbirrazzuoli et al (70) have applied isoconversional kinetic analysis to the vaporization kinetics of alachlor and metolachlor and found that the obtained activation energies are consistent with the respective enthalpies of vaporization. Hazra et al (71) have used DSC and TGA to study vaporization kinetics of some essential oils and their key components.…”
Section: Kineticsmentioning
confidence: 90%